The Integral Role Of Doctors And Nurses In Diabetes Care: From Diagnosis To Treatment (Journal of Namibian Studies : History Politics Culture, 2022)
This article explores the integral role of doctors in the comprehensive care of diabetes patients, covering aspects from diagnosis to treatment. Doctors and nurses serve as frontline providers, diagnosing diabetes through thorough assessments and diagnostic tests. Subsequently, they develop personalized treatment plans, incorporating lifestyle modifications, medications, and insulin therapy as necessary. Central to their role is patient education, empowering individuals with the knowledge to manage their condition effectively. Through ongoing monitoring, doctors ensure optimal glycemic control and prevent complications, collaborating with other healthcare professionals as needed.